LEFT ATRIAL STRAIN BY SPECKLE TRACKING ECHOCARDIOGRAPHY IS NOT PREDICTED FUNCTIONAL CAPACITY IN HYPERTENSIVE POPULATION WITH PRESERVED SYSTOLIC FUNCTION AND NORMAL RESTING LEFT ATRIAL PRESSURE - Gilang Mauladi Rahman; Muhammad Aminuddin; Budi S Pikir (The Indonesian Heart Association, 2019)
Abstract Background: Hypertension is associated with diastolic dysfunction and impaired exercise capacity. LA has a substantial role to provides an optimal left ventricle diastolic filling. In this study, we aimed to assess the left atrial strain through STE as a predictor of functional capacity in the hypertensive population. Methods: A total of 43 hypertensive women (mean age 50 ± 5.2 y.o; BMI 28.5± 4.1 Kg/m2) consecutively enrolled in this study. Patients with LVEF <50% or significant valvular pathology excluded. Two-dimensional STE performed to asses LA strain parameters, including PALS , PACS, and conduit strain. Functional capacity assessed by treadmill stress test using Bruce protocol. Result: Mean PALS, PACS, and conduit strain in this study was lower than reference normal value 25.8%< 39%; 12.4% <17%; 13.5% <23%, respectively). All of the subjects had a preserved systolic function (mean LVEF 72.5 ± 7.6%) and normal resting LA pressure (mean PCWP 11.96 ± 2.09). Left atrial strain parameters value in the low-fair functional capacity group was not significantly different to average-good functional capacity group (p>0.05). Left atrial strain parameters value was not significantly correlated to exercise duration and achieved METS (P>0.05). Conclusion: LA strain value in this study was below the standard reference limit. LA strain cannot predict functional capacity in the hypertensive population with preserved ejection fraction and normal resting LA pressure.